Quantum Thermalization Dynamics of Fermi Gases Quenched to the BEC‐BCS Crossover - Licheng Yi; Shuxian Yu; Meimei Wu; Shujin Deng; Haibin Wu (Advanced Science)
Abstract Understanding nonequilibrium dynamics of strongly interacting quantum systems represents one of the most challenging problems in many‐body physics. Here, quantum thermalization dynamics are explored in real‐time in an ultracold Fermi gas suddenly quenched to the BEC‐BCS crossover. When quenched to unitarity, it is observed that the cloud size remains unchanged in the early evolution while the momentum distribution emerges two prethermal states with a lifetime difference of two orders of magnitude in the early and intermediate stage before very slowly evolving to the final stationary state. It is revealed that a crossover momentum, at which the momentum distribution remains nearly unchanged, is determined by the thermal wavelength at high temperatures and the Fermi momentum while at low temperatures. It is identified that the universal prethermal dynamics scaling where momentum distributions with different temperatures collapse onto one curve. When quenched to the BEC side, the thermalization rapidly relaxes into a prethermal state and exhibits the low energy oscillation related to the molecular bound states. This work provides benchmarks for the study of quantum thermalization in strongly interacting fermionic many‐body systems.